Fundamental aspects of selenium and selenoprotein biochemistry: applied value in oncology - I. V. Stanoevich; V. V. Khvostovoy; D. V. Petrochenko; A. Yu. Salamatina; V. A. Ioutsi; Yu V. Furman; N. L. Lysovolenko; I. V. Ermilov (Сибирский онкологический журнал)
The purpose of the study was to carry out a systematic analysis of the data available in the modern literature on the essentiality of selenium in biological systems and the importance of selenoproteins in oncogenesis.Material and Methods. The publications were analyzed using Scopus (415), PubMed (521), Web of Science (139), eLibrary.ru (240) databases. To obtain full-text documents, the electronic resources PubMed Central (PMC), Science Direct, Research Gate, eLibrary.ru were used.Results. The need to use selenium compounds for the prevention and treatment of malignant neoplasms is controversial, and some selenoproteins have demonstrated a permissive role in oncogenesis, thus requiring further in-depth study in neoplasms of various histogenesis.Conclusion. It is necessary to continue comprehensive molecular studies of bioorganic selenium compounds at the morphological, ultrastructural and biochemical levels in tumors of various localizations, depending on the genetic characteristics of the studied population and the geochemical characteristics of the region.